A Smart IoT Node using a Hybrid Edge-Computing Strategy for Environmental Multiparameter Sensing - Antunes, André Mendes (2021)
The Internet of Things (IoT) has been growing at an immense pace over the last few years and there are no predictions of slowing down anytime soon, but most importantly, not only has it been growing in size but it has also been growing in capabilities, performance and diversity. Diversity is incredibly important but also fracturing, in this context. As IoT sensor nodes get more performant and diverse, their adaptability and reconfigurability ends up being lost in the search for ultimate performance. As a way to unify these individual single purpose sensor nodes, a need and an opportunity present themselves to develop a singular multi-parameter, multi-sensor IoT node, that can make use of the latest reconfigurable technology to adapt itself to the requirements of each type of sensor, while maintaining the very high performance and precision of dedicated sensor nodes. This dissertation work will thus focus on developing an architecture and building a prototype circuit board for a multi-sensor, reconfigurable IoT node based on a state-ofthe- art System-on-Chip (SoC) with extremely high resolution measurement capabilities, which can interface with virtually any type of existing sensor. This architecture and prototype are intended to serve as a stepping stone in the path to develop a capable IoT node which can interface with a wider range of sensor and have a higher precision than what is currently available